ANALISIS KELAYAKAN FINANSIAL SELADA (Lactuca Sativa L.) DENGAN SISTEM HIDROPONIK NFT (Nutrient Film Technique) DI PERKOTAAN (STUDI KASUS DI KOTA KENDARI) - Hasnun, Hasnun; Mappasomba, Musadar; Suriana, Suriana (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2025)
This study aims to determine the financial feasibility of lettuce (Lactuca sativa L.) farming using the NFT (Nutrient Film Technique) hydroponic system in urban areas (case study in Kendari City). The study was conducted from June to November 2024. The population in this study consists of all farmers engaged in hydroponic farming using the NFT system in Kendari City. The sample size was determined based on information from the Kendari City Agriculture Department in 2021, totaling 10 farmers. Data sources include primary and secondary data. Data collection techniques include observation, questionnaires, documentation, and literature review. The research variables included respondent characteristics, income during one harvest season, including production costs and revenue. Data analysis in this study used the production cost formula, revenue, income, and R/C Ratio. The results of the study indicate that farming can be considered viable, given that the R/C ratio analysis yielded a value of 2.43. The average total cost of farming was Rp. 2,960,751, while the revenue was Rp. 7,200,000, and the net income was Rp. 4,230,249 per planting season.